Freedom of expression - Stearman, Kaye (Wayland Hove, 1993)
"Freedom of Expression" by Kaye Stearman, published in 1994. This book is part of the 'Human Rights' series and provides an overview of the concept of freedom of expression, its importance in democratic societies, and the challenges it faces globally. It discusses various aspects such as censorship, media freedom, and the balance between free speech and societal responsibilities. Given its publication date, the book may not cover recent developments in the field of freedom of expression, especially concerning digital media and the internet. However, it offers a foundational understanding of the topic and its significance in upholding human rights. For more recent analyses, you might consider looking into works by authors like David Kaye, who have explored contemporary issues related to freedom of expression in the digital age.